The Effect of Work Environment on Work Stress at PT. Timbang Deli Indonesia Verdant Biosience (Case Study: Seed Production and Selection) - Meidy Sriska; Risa Kartika Lubis (Institute of Computer Science (IOCS), 2020)
This study aims to determine the effect of the work environment on work stress at PT. Timbang Deli Indonesia Verdant Biosience (Case Study: Seed Production and Selection). The sample used in this study were employees at PT. Timbang Deli Indonesia Verdant Biosience (Case Study: Seed Production and Selection), the number of samples is 35 people. The results of this study indicate that the independent variable, namely the work environment factor (X) has a positive and significant effect on employee work stress at PT. Timbang Deli Indonesia Verdant Biosience (Case Study: Seed Production and Selection).